1989
DOI: 10.1254/jjp.51.291
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-induced villous damage in the rat duodenum.

Abstract: Abstract-A single s.c. administration of histamine dose-dependently (5-20 mg/ kg) induced villous damage of the proximal duodenum in 24-hr fasting rats. Time course studies indicate that histamine (20 mg/kg) induced severe exfoliation of the epithelial cells at the villous tips of the duodenal mucosa 0.5 hr after administration. The damage, however, tended to heal with time, and recovery was nearly complete 8 hr later. This villous damage was significantly inhibited by pretreatment with sodium bicarbonate give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This is surprising since the gut is frequently in contact with this amine, owing to the fact that it is present in many foods (1,2). The few studies on the effects of histamine on intestinal mucosa were done in animals (7,8), and the route of administration used in those studies did not correspond to the physiologic conditions of histamine ingestion. Nevertheless, the results demonstrate that histamine can modify intestinal architecture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is surprising since the gut is frequently in contact with this amine, owing to the fact that it is present in many foods (1,2). The few studies on the effects of histamine on intestinal mucosa were done in animals (7,8), and the route of administration used in those studies did not correspond to the physiologic conditions of histamine ingestion. Nevertheless, the results demonstrate that histamine can modify intestinal architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results demonstrate that histamine can modify intestinal architecture. Tanaka et al demonstrated that a single subcutaneous dose of histamine (20 mg/kg) in rats induced villous changes in the duodenum, consisting of severe exfoliation of epithelial cells and exposure of the lamina propria (8). These changes were reversed within 8 h, indicating rapid mucosal repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two specimens per animal were analysed by an observer unaware of the experimental procedures. The examined intestinal surface was scored into four categories depending on the degree of mucosal changes, according to a modified scale proposed by Tanaka et al . (1989).…”
Section: Methodsmentioning
confidence: 99%